Al-Kalimãt Dzãtu Ashlin Arabiyyin Fî Al-Mu’jam Al-Mãdûrî Wa Al-Istifãdah Minhã Fî Ta’lîm Al-Mãduriyyîn - Farwizah Ma’sum; Arif Taufikurrohman (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2021)
تهدف هذه الدراسة إلى معرفة الكلمات ذات أصل عربي في معجم اللغة المادورية من حرف I إلى حرف S لسهولة الدراسة لدى الطلاب المبتدئين، وإزالة الفهم الخاطئ لديهم بأن تعلم اللغة العربية شيء صعب لاختلاف النطق والحروف بين لغتهم الأم واللغة الثانية. ويتم إنجاز هذه الدراسة على منهج علمي وهو: المنهج الوصفي التحليلي، وقد أثبتت الدراسة أن في معجم مادورا من حرف I إلى حرف S مائة أربعة وعشرون كلمة ذات أصل عربي. وذلك بجمع الكلمات ذات أصل عربي في اللغة المادورية مستعينا بمعجم اللغة المادورية، وتحليلها نطقا ومعنى. وأما من جهة المعنى فقد يكون باقيا على معناها الأصلي أو حصل تغيير معنى بعض الكلمات إلى المعنى الأضيق أو الأوسع أو مخالف للمعنى الأصلي. وبيان كيفية الاستفادة منها في تعليم اللغة العربية للمادوريين خاصة وتسهيل المتعلمين المادوريين في تعليم اللغة العربية. This study aims to Arabic words of origin in the Madura language dictionary from letter I to letter S to facilitate Madura beginners in study, and delete wrong understanding to them that learning Arabic something difficult despite the differences in pronunciation and letters between native and second languages. This study was carried out for the scientific method that is: descriptive analysis method, and study have proven that in the Madura dictionary from letter I to letter S there are 124 arabic words. And that is by collecting Arabic words of origin in Madura with the help of the Madura language dictionary and analyzed in the form of speech and meaning in some words narrower meanings or wider or contrary to its original meaning. And explanation of ways how to benefit from it in learning Arabic for madurese in particular and make it easier on Madura native students in learning Arabic.